2020
DOI: 10.3389/fpsyt.2020.00386
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and Influencing Factors of Anxiety and Depression Symptoms in the First-Line Medical Staff Fighting Against COVID-19 in Gansu

Abstract: BackgroundThe outbreak of novel coronavirus pneumonia (COVID-19) has brought enormous physical and psychological pressure on Chinese medical staff. It is extremely important to understand the prevalence and influencing factors of anxiety and depression symptoms in first-line anti-epidemic medical staff and their coping styles for these negative emotions.MethodsA cross-sectional survey was conducted in Gansu (China), with a questionnaire packet which consisted of the self-rating anxiety scale (SAS), self-rating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
226
3
25

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(274 citation statements)
references
References 31 publications
20
226
3
25
Order By: Relevance
“…A prior study in China documented the prevalence rates of anxiety (46.04%) and depression (44.37%) were high among HCWs during the COVID-19 pandemic [7]; here, the prevalence of depression was somewhat lower and that of anxiety somewhat higher. Another study of anxiety and depression among first-line medical staff in China showed the prevalence estimates of anxiety and depression were 45.6%, and 11.4%, respectively [34]. A study in India of HCWs suggested the prevalence of anxiety symptoms (17.7%) requiring additional evaluation and depressive symptoms (11.4%) needing treatment [35] are lower than those in the present study.…”
Section: Comparing With Other Studiescontrasting
confidence: 67%
“…A prior study in China documented the prevalence rates of anxiety (46.04%) and depression (44.37%) were high among HCWs during the COVID-19 pandemic [7]; here, the prevalence of depression was somewhat lower and that of anxiety somewhat higher. Another study of anxiety and depression among first-line medical staff in China showed the prevalence estimates of anxiety and depression were 45.6%, and 11.4%, respectively [34]. A study in India of HCWs suggested the prevalence of anxiety symptoms (17.7%) requiring additional evaluation and depressive symptoms (11.4%) needing treatment [35] are lower than those in the present study.…”
Section: Comparing With Other Studiescontrasting
confidence: 67%
“…A meta-analysis showed that the prevalence of anxiety and depression in healthcare workers who provide care for COVID-19 patients was 23.2% and 22.8% respectively (19). The studies conducted in other parts of the world indicate that the prevalence of anxiety is about 11.3 to 50% (21,4,20). The ndings of the present study report that it is slightly higher than this range.…”
Section: Discussioncontrasting
confidence: 40%
“…Many studies observed high rates of anxiety, stress symptoms, mental disorders, and post-traumatic stress among the healthcare workers during the pandemic. [9][10][11][12][13][14][15] Primary care services are slightly superior as compared to traditional health care. In the Brazilian health system, the first contact of patients occurs with professionals of the primary care service such as physicians, nurses and dentists.…”
Section: Introductionmentioning
confidence: 99%